Cloning, Expression, Purification, and Characterization of Glutaredoxin from Antarctic Sea-Ice Bacterium Pseudoalteromonas sp. AN178. (7th July 2014) - Wang, Quanfu; Hou, Yanhua; Shi, Yonglei; Han, Xiao; Chen, Qian; Hu, Zhiguo; Liu, Yuanping; Li, YuJin
Abstract : Glutaredoxins (Grxs) are small ubiquitous redox enzymes that catalyze glutathione-dependent reactions to reduce protein disulfide. In this study, a full-length Grx gene ( Ps Grx) with 270 nucleotides was isolated from Antarctic sea-ice bacterium Pseudoalteromonas sp. AN178. It encoded deduced 89 amino acid residues with the molecular weight 9.8 kDa. Sequence analysis of the amino acid sequence revealed the catalytic motif CPYC. Recombinant Ps Grx (r Ps Grx) stably expressed in E. coli BL21 was purified to apparent homogeneity by Ni-affinity chromatography. r Ps Grx exhibited optimal activity at 30°C and pH 8.0 and showed 25.5% of the activity at 0°C. It retained 65.0% of activity after incubation at 40°C for 20 min and still exhibited 37.0% activity in 1.0 M NaCl. These results indicated that r Ps Grx was a typical cold active protein with low thermostability.